2004
DOI: 10.1111/j.1048-891x.2004.14046.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hepatocyte growth factor levels of epithelial ovarian cancer cyst fluids with benign ovarian cysts

Abstract: Hepatocyte growth factor (HGF) is known to take role in oncogenesis and tumoral behavior of the tumors of the organs that contain mesenchymal and epithelial cells together. This study aims to compare HGF levels in cyst fluids of epithelial ovarian cancer and benign ovarian cysts and look for the role of HGF in ovarian carcinogenesis. Twenty-four consecutive patients with ovarian cancer and 34 with benign cysts of ovary were recruited prospectively at Gynecologic Oncology Departments of SSK Ankara Maternity Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…We have shown that in ovarian cancer cells HGF mRNA is expressed, together with its receptor Met, to positively regulate cell proliferation 146 . Consistent with this, a high level of HGF was found in malignant ovarian cystic and ascitic fluid as compared to benign ovarian cysts 147,148 . Interestingly, autocrine HGF‐Met activity and altered downstream signaling have been observed also in OSE cells from ovarian cancer prone women (FH‐OSE) 146,149 .…”
Section: Hepatocyte Growth Factorsupporting
confidence: 55%
“…We have shown that in ovarian cancer cells HGF mRNA is expressed, together with its receptor Met, to positively regulate cell proliferation 146 . Consistent with this, a high level of HGF was found in malignant ovarian cystic and ascitic fluid as compared to benign ovarian cysts 147,148 . Interestingly, autocrine HGF‐Met activity and altered downstream signaling have been observed also in OSE cells from ovarian cancer prone women (FH‐OSE) 146,149 .…”
Section: Hepatocyte Growth Factorsupporting
confidence: 55%
“…18 HGF is found at significantly high levels in malignant ovarian cystic and ascitic fluids from ovarian carcinomas compared to that of benign ovarian cysts and stimulates the migration of ovarian carcinoma cells. 4,19 HGF is known as a survival factor that offers protection from apoptosis. 20 However, it was also reported that treatment with HGF surprisingly enhanced apoptosis of ovarian cancer cells with low doses of the chemotherapeutic drugs cisplatin and paclitaxel in vitro and in vivo, 21,22 and this effect was mediated by p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many growth factors that can contribute to such a phenotypical modulation of cancer cells, Hepatocyte growth factor (HGF) has been known to play a predominant role in ovarian cancer by stimulating growth, invasiveness, and metastatic capability of cancer cells. [3][4][5] HGF, a stromal-derived functional growth factor, 6 has been associated with metastases in many types of human cancers. 7 HGF specifically binds to its receptor c-met, activating a complex set of intracellular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…High peritoneal levels of HGF in the presence of endometriosis may trigger similar imbalance, resulting in mitogenic activity of OSE. This is supported by the fact that high levels of HGF are also present in the fluid of malignant ovarian cysts compared with benign cysts (88) and that Met is expressed in high levels in 28% of epithelial ovarian cancer and levels of expression increase in differentiated ovarian carcinomas compared with normal OSE (89,90). In addition, in patients with hereditary ovarian cancer, enhanced stability of c-Met and HGF secretion are implicated as early factors in ovarian carcinogenesis (91).…”
Section: Tgf-bmentioning
confidence: 96%